Maska czy gęba? Operetka Witolda Gombrowicza w kontekście komedii dell’arte - Bąkowska, Nadzieja (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The article is an attempt at placing Operetka (Operetta) in the context of commedia dell’arte by comparing the basic structural and ideological characteristics of Witold Gombrowicz’s drama with the key traits of the commedia dell’arte genre. The author of Ferdydurke, who coined the phrase przyprawiać (komuś) gębę (put the screws to someone’s mug), brings to the grotesque distortion any manifestations of form domination both in life and in art. Ironically, it is the elements of Operetka, related to commedia dell’arte – a thoroughly conventionalised and schematised genre, that become the tool for a sort of removal of mask or mug. Given the mask, protagonists are given “a mug”, and cannot be themselves, they can only be what is allowed by the mask they were given and so they become its prisoner, in a way. The only antidote to “the mug” is nudity that frees one from any mask that forces them to play the designated roles. The article aims to present the relationship between Operetka and the commedia dell’arte genre, with particular emphasis on analysing the Gombrowicz’s concept of form against the convention of mask and costume in the commedia dell’arte, and on the “nudity” vs. “mask” opposition that focuses the drama’s main artistic and existential issues, while it is also precisely the point where the relationship between Gombrowicz’s work and Italian commedia dell’arte is seen most clearly.